STRATEGI KESANTUNAN BERBAHASA KOREA STUDI KASUS PRAMUWISATA DENGAN WISATAWAN KOREA DI DAERAH PARIWISATA DI BALI - Sukartana, I Gede (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2015)
This research based on impoliteness by tour guide in speech with Korean tourists. It is because of differences of culture between tour guides and Korean tourist. Impoliteness of speech can make threatening face of tour guide so that need to applied strategy of politeness with the intention to minimize impoliteness and face saving of tour guide. This research also discuss about verbal unit, function and meaning of politeness. The data are in the form of dialogs between tour guide and Korean tourists in tour journey in Bali. Data analyzed by qualitative research based on case studies.These results indicate that tour guides implementation four face-saving strategy with the aim to avoiding impoliteness. Politeness guides realized by the form of units of verbal words, idioms, and sentences through the use of speech variation. The function of politeness expressed by functions of speech acts and politeness meaning refers to the intention of the speech uttered by the tour guides. The theory cooperation by Grice's (1975) and the theory of politeness Leech (1983) is used to address the the application of maxims of politeness in analysis fuctions and meaning of tour guide politeness.
Keywords: speech, speech acts, politeness, tour guide, Korean tourists